Catalisadores de Pd/Al2O3 modificados com La: preparação, caracterização e propriedades catalíticas nas reações de reforma a vapor e autotérmica do metano - Cassinelli, Wellington Henrique (Universidade Federal de São Carlos, 2010)
The Pd catalysts were prepared by wet impregnation method of the supports using an aqueous solution of palladium nitrate. (x)La2O3-Al2O3 carriers, with x = 0 to 20 wt %, were obtained by wet impregnation and sol gel methods. The supports and catalysts were characterized by N2 physisorption, X-ray diffraction, thermogravimetry, temperature-programmed reduction, Fourier transformed infrared spectroscopy of the adsorbed CO, X-ray photoelectron spectroscopy, transmission electron microscopy and dehydrogenation of cyclohexane reaction. The La2O3 presence on the carriers promotes a decrease in the Eaap and an increase in the TOFap and CH4 consumption values at 510 °C in the steam reforming of CH4 reaction. This increase in activity was related to Pdº*Pd+-OLa interfacial species type formation. These interfacial species promote the formation of Pd° sites of higher electron density, most activ e to C-H bond cleavage, and are also likely to be oxidized by H2O and CO2 co-reagents, promoting the O * transfer to the metal surface, which act on the oxidation of chemisorbed carbon (C *). This fact makes that the determining steps process to be more balanced, promoting a greater of CH4 accessibility to the Pd surface. The nature of the supports has a high influence on the properties of Pd catalysts in autothermal reforming of CH4 reaction (ATR). The Pd/Al catalysts showed a high deactivation in the ATR, due to strong agglomeration of Pd crystallites during the time the catalyst was maintained at 800 °C. For La 2O3 containing catalysts, the Pdº*Pd+-O-La interfacial species type formation promoted a higher activity and stability in ATR. However, was observed the formation of graphitic carbon type for Pd/12LaAl samples. The interfacial species promote both an increase in the CH4 activation rate, as in the removal of the C* species formed during CH4 activation. However, the CH4 activation and C* formation rate should be higher than diffusion or removal carbon rate. This effect coupled with the suitable particle size formed during the ATR tests results in a greater C* accumulation and growth in the filaments form.
PD/AL2O3 catalysts modified with la: preparation, characterization and catalytic properties in the steam and autothermal reforming of methane reactions
Keywords: Catálise heterogênea; Sol-Gel; Reações de reforma do CH4; XPS; Espectroscopia no infravermelho do CO adsorvido; CIENCIAS EXATAS E DA TERRA::QUIMICA